Analysis of the process leading to termination of pregnancy in the third trimester - Ömer Gökhan Eyisoy; Lütfiye Uygur; Ümit Taşdemir; Çağdaş Özgökçe; Büşra Cambaztepe; Oya Demirci (Perinatal Medicine Foundation, 2023)
Objective: To evaluate fetal anomalies and processes leading to termination of pregnancy in the third trimester. Methods: The study includes all cases who underwent termination of pregnancy after 28 weeks of gestation due to fetal anomalies between 2017 and 2022. Results: Forty four of third trimester terminations were carried out in our clinic due to fetal anomalies incompatible with life or associated with severe sequelae. Structural anomalies including 35 (79.5%) cases were the most common reason of terminations followed by chromosomal or genetic abnormalities in 8 (18.2%) cases and intrauterine cytomegalovirus infection in 1 (2.3%) case. The processes leading to the third trimester termination were evaluated by dividing 44 patients into 5 groups. (1) Delayed diagnosis due to inadequate prenatal care (25 patients, 56.8%); (2) patients diagnosed with late-onset findings (5 patients, 11.4%); (3) patients with abnormal findings in prenatal care or history but delayed diagnosis (5 patients, 11.4%); (4) patients with abnormal findings requiring further evaluation (4 patients, 9.0%); (5) patients with a definitive diagnosis but latency in the decision of family for termination of pregnancy (5 patients, 11.4%). Conclusion: Termination of pregnancy in the third trimester has an important role in countries where unfollowed pregnancies are common and access to health services is poor due to low socio-economic status.